Effect of Clonally Expanded PD‐1highCXCR5–CD4+ Peripheral T Helper Cells on B Cell Differentiation in the Joints of Patients With Antinuclear Antibody–Positive Juvenile Idiopathic Arthritis. Issue 1 (15th December 2021) - Fischer, Jonas; Dirks, Johannes; Klaussner, Julia; Haase, Gabriele; Holl‐Wieden, Annette; Hofmann, Christine; Hackenberg, Stephan; Girschick, Hermann; Morbach, Henner
Abstract : Objective: Antinuclear antibody (ANA)–positive juvenile idiopathic arthritis (JIA) is characterized by synovial B cell hyperactivity, but the precise role of CD4+ T cells in promoting local B cell activation is unknown. This study was undertaken to determine the phenotype and function of synovial CD4+ T cells that promote aberrant B cell activation in JIA. Methods: Flow cytometry was performed to compare the phenotype and cytokine patterns of PD‐1 high CD4+ T cells in the synovial fluid (SF) of patients with JIA and T follicular helper cells in the tonsils of control individuals. TCRVB next‐generation sequencing was used to analyze T cell subsets for signs of clonal expansion. The functional impact of these T cell subsets on B cells was examined in cocultures in vitro. Results: Multidimensional flow cytometry revealed the expansion of interleukin‐21 (IL‐21) and interferon‐γ (IFNγ)–coexpressing PD‐1 high CXCR5–HLA–DR+CD4+ T cells that accumulate in the joints of ANA‐positive JIA patients. These T cells exhibited signs of clonal expansion with restricted T cell receptor clonotypes. The phenotype resembled peripheral T helper (Tph) cells with an extrafollicular chemokine receptor pattern and high T‐bet and B lymphocyte–induced maturation protein 1 expression, but low B cell lymphoma 6 expression. SF Tph cells, by provision of IL‐21 and IFNy, skewed B cell differentiation toward a CD21 low/– CD11c+ phenotype in vitro. Additionally, SF Tph cell frequencies correlated with the appearance of SF CD21 low/– CD11c+CD27–IgM– double‐negative (DN) B cells in situ. Conclusion: Clonally expanded CD4+ Tph cells accumulate in the joints of ANA‐positive JIA patients and, in particular, promote CD21 low/– CD11c+ DN B cell differentiation. The expansion of Tph cells and DN B cells might reflect the autoimmune response in the joints of ANA‐positive JIA patients.